Intersecting urban and traffic models for virtual reality environments with realistic traffic behaviour - Singler, Oliver; Thiebes, Leon; Fedior, Marco; Disse, Leonie; Plank-Wiedenbeck, Uwe (International Conference “Environmental Engineering”, 2023)
A novel framework for modelling urban infrastructure and traffic for Virtual Reality with a focus on datadriven scalability and integration of simulated realistic driving behaviour is presented. Publicly available terrain and building models are automatically fused to recreate a representative traffic intersection of the German city of Erfurt. The generated 3D model is used to incorporate longitudinal road inclines in a microscopic traffic simulation. The simulated vehicle trajectories are visualized on the 3D model in a Virtual Reality environment, resulting in an environment based on a real intersection with realistic traffic behaviour. The developed framework is easy to use and can be adapted to other cities with similar data available. The Virtual Reality environment can be used, among others, for the evaluation of traffic safety, urban planning, and emerging technologies.